Design Of Sunlight, Humidity, And Temperature Measurement Systems With Data Acquisition For Iot-Based Solar Panel Placement - Widianto Utomo, Satrio; Minarto; Kaniawulan , Ismi (RISTEC : Research in Information Systems and Technology, 2023)
The Internet of Things (IoT) is a concept a imed at expanding the benefits of continuous internet connectivity. IoT can be utilized for monitoring the intensity of light, temperature, and air humidity in the surroundings to determine suitable locations for the pla cement of sola r panels. Sola r panels are made of semiconductor materia ls capable of converting sola r energy into electricity. The prima ry issue with using sola r panels is that the power output they produce depends on the intensity of light captured by the sola r panel. Additiona lly, the temperature and air humidity a round the sola r panel also influence its performance. The objective of this resea rch is to create a system for measuring the intensity of sunlight, humidity, and temperature for the placement of IoT-ba sed sola r panels using LDR and DHT 11 sensors. The development of this system involves the use of the Prototyping Method. The device's design incorporates the NodeMCU ESP32 microcontroller, and monitoring is conducted through a sma rtphone using the Blynk application. The LDR and DHT 11 sensors are connected to the NodeMCU ESP32's GPIO as data receivers. A WiFi network is used to transmit intensity of light, temperature, and humidity data from the NodeMCU ESP32 to the smartphone, where it is displayed through the Blynk application. This research is beneficial for identifying the most suitable locations for solar panel placement.